2022
DOI: 10.1111/dth.15433
|View full text |Cite
|
Sign up to set email alerts
|

The role of SARS‐CoV‐2 infection and its vaccines in various types of hair loss

Abstract: The prevalence of hair loss has increased during COVID‐19. In this study, we review the current literature on incidence and characteristics of various types of COVID‐19‐related and COVID‐19‐vaccine‐ related hair loss including telogen effluvium, alopecia areata, friction alopecia and anagen effluvium. Regarding most of them, the more severe the infection, the more profound and prolonged the course of alopecia. However, the most important issue is reassuring the patients of the non‐serious nature of this compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…Many case reports and studies of hair involvement reported after COVID‐19 vaccination have been published in the literature. 35 , 36 , 37 Nonetheless, since our study focused on cutaneous reactions, hair involvement after COVID‐19 vaccination was not examined separately. However, the current study also had several strengths, such as more than 95% of non‐local cutaneous reactions being diagnosed by a dermatologist and the participants being questioned through one‐to‐one interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports and studies of hair involvement reported after COVID‐19 vaccination have been published in the literature. 35 , 36 , 37 Nonetheless, since our study focused on cutaneous reactions, hair involvement after COVID‐19 vaccination was not examined separately. However, the current study also had several strengths, such as more than 95% of non‐local cutaneous reactions being diagnosed by a dermatologist and the participants being questioned through one‐to‐one interviews.…”
Section: Discussionmentioning
confidence: 99%
“…AA is an autoimmune-mediated hair loss with an estimated incidence of around 2% in the community [8]. Genetic factors, autoimmune diseases, stress, atopic diathesis, nutritional deficiency, hormonal changes, infections, and vaccination have been implicated in the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of AA have been identified after vaccination against influenza virus, hepatitis B virus, herpes zoster virus, human papillomavirus, Japanese encephalitis, and Clostridium tetani [6,7]. During this pandemic, acute SARS-CoV-2 infection has been associated with the development of telogen effluvium, alopecia areata, friction alopecia, and anagen effluvium [8]. AA following various SARS-CoV-2 vaccine injections was rarely reported, however [1,6,7,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of hair loss have been reported after COVID-19 vaccination, including alopecia areata and telogen effluvium [ 117 121 ]. Alopecia areata has been noted either with rapid onset after vaccination or recurrences of alopecia areata after COVID-19 vaccination [ 117 122 ].…”
Section: Cutaneous Reactions To Covid-19 Vaccinesmentioning
confidence: 99%